Native and introduced fish community structure in a freshwater swamp forest: Implications for conservation and management. Issue 1 (27th December 2018) - Ho, Jonathan K.I.; Ramchunder, Sorain J.; Memory, Andrew; Tan, Heok Hui; Yeo, Darren C.J.
Abstract: Freshwater swamp forests are poorly studied but highly threatened freshwater habitats, especially in Southeast Asia. Very little is known about the environmental factors associated with the assembly and spatial distribution of fish communities in these acid‐water habitats, although such knowledge is of immense importance for conservation and management. Fish assemblages in 40 stream sites throughout the Nee Soon Swamp Forest, Singapore, were surveyed using push nets from October 2013 to November 2014. The Nee Soon Swamp Forest is the last substantial remnant of freshwater swamp forest habitat in Singapore, and today it is the only refuge for many of the native forest‐specialist freshwater fish species. The overall diversity and richness of the fish community are positively correlated with depth, stream order, and canopy cover, and are negatively correlated with distance to a connected reservoir, mean velocity, and silt substrate. Observed patterns indicate that three main communities exist, each with distinct associated species and environmental parameters. One is a novel community of introduced species and non‐forest specialist native species found only at the outskirts (downstream portion) of the swamp forest, close to a reservoir connection that drains the swamp, whereas the other two communities are found in the interior of the swamp forest and harbour mostly forest‐specialist native species of restricted distribution and high conservation value. The community on the outskirts may be a potential route for introduced species to spread and establish populations deeper within the swamp forest. At present the native community within the swamp forest appears to be healthy, but constant monitoring is needed to ensure that the native community is not threatened by loss of habitat or introduced species.